The psychologist's companion : a guide to scientific writing for students and researchers - Sternberg, Robert J. (Cambridge University Press, 2003)
"The Psychologist's Companion, 4th edition, is intended to be a definitive guide to scientific writing for students and researchers. It covers a wealth of topics, including misconceptions about psychology papers, steps in writing library research papers, steps in writing experimental research papers, rules for writing psychology papers, commonly misused words, Internet resources, American Psychological Association guidelines for writing psychology papers, guidelines for data presentation, references for psychology papers, standards for evaluating psychology papers, guidelines for submitting papers to journals, how to win acceptances of papers by psychology journals, how to write grant and contract proposals, how to find book publishers, and how to write lectures and articles. The book contains a sample psychology paper as well as an appendix relevant to writing for British and European journals. The book is written in a lively and witty style that will make it easy reading for even the busiest student or professional."--Jacket